The World Wide Web of Work A history in the making - van der Linden, Marcel (Work Around the World, 2023)
Global Labour History has rapidly gained ground as a field of study in the 21st century, attracting interest in the Global South and North alike. Scholars derive inspiration from the broad perspective and the effort to perceive connections between global trends over time in work and labour relations, incorporating slaves, indentured labourers and sharecroppers, housewives and domestic servants. Casting this sweeping analytical gaze, The World Wide Web of Work discusses the core concepts 'capitalism' and 'workers', and refines notions such as 'coerced labour', 'household strategies' and 'labour markets'. It explores in new ways the connections between labourers in different parts of the world, arguing that both 'globalisation' and modern labour management originated in agriculture in the Global South and were only later introduced in Northern industrial settings. It reveals that 19th-century chattel slavery was frequently replaced by other forms of coerced labour, and it reconstructs the laborious 20th-century attempts of the International Labour Organisation to regulate labour standards supra-nationally. The book also pays attention to the relational inequality through which workers in wealthy countries benefit from the exploitation of those in poor countries. The final part addresses workers' resistance and acquiescence: why collective actions often have unanticipated consequences; why and how workers sometimes organise massive flights from exploitation and oppression; and why 'proletarian revolutions' took place in pre-industrial or industrialising countries and never in fully developed capitalist societies.